Novel functions of peroxiredoxin Q from Deinococcus radiodurans R1 as a peroxidase and a molecular chaperone. Issue 2 (11th December 2018) - Cho, Chuloh; Lee, Gun Woong; Hong, Sung H.; Kaur, Shubhpreet; Jung, Kwang‐Woo; Jung, Jong‐Hyun; Lim, Sangyong; Chung, Byung Yeoup; Lee, Seung Sik
Abstract : Deinococcus radiodurans R1 is extremely resistant to ionizing radiation and oxidative stress. In this study, we characterized DR0846, a candidate peroxiredoxin in D. radiodurans . DR0846 is a peroxiredoxin Q containing two conserved cysteine residues. DR0846 exists mainly in monomeric form with an intramolecular disulfide bond between the two cysteine residues. We found that DR0846 functions as a molecular chaperone as well as a peroxidase. A mutational analysis indicates that the two cysteine residues are essential for enzymatic activity. A double‐deletion mutant lacking DR0846 and catalase DR1998 exhibits decreased oxidative and heat shock stress tolerance with respect to the single mutants or the wild‐type cells. These results suggest that DR0846 contributes to resistance against oxidative and heat stresses in D. radiodurans . Abstract :